Tathwīru Kitābi al-Jaibi ka Mushochibi Kitābi al-Lughah al-‘Arabiyyah lī ash-Shoffi as-Sābi’ li Tarqiyati al-Mahārah al-Lughāwiyyah fī Madrasah al-Khamīdiyyah al-Mutawassithah al-Islāmiyyah - Fayruza, Aida Zavirah; Khasairi, Moh.; Ahsanuddin, Mohammad (Universitas Negeri Malang, 2024)
Teaching Arabic at the middle school level has a crucial role in shaping students’ Arabic language skills, especially in the seventh grade. In view of the challenges and needs in the learning process, the researcher tried to improve students’ abilities to understand and apply these challenges. This research seeks to develop the pocketbook as a companion to the Arabic language book to improve language skills at Al-Hamidiyah Islamic Middle School, describe its validity, and the effectiveness of its use. The results of the research in this study are (1) This development research used the Borg & Gall development model, and the steps taken by the researcher were needs analysis, desk study, field study, material selection, product development, expert testing, correction, product trial and final product improvement. The development of this educational material led to the creation of the pocketbook as a companion to the Arabic language book consisting of three units, (2) Validity testing was conducted which includes expert testing in two main aspects: validity of the material and validity of the methods. The results of the material validity test were 70%, while the results of the methods validity test were 90.8%. (3) The pocketbook received the category of effective for use as an educational tool for seventh grade students at Al Hamidiya Islamic Middle School. The test results show that the calculated t value is larger than the t table, that is, the calculated t is -24.948 while the t table is 2.060. إن تعليم اللغة العربية على مستوى المدرسة المتوسطة له دور حاسم في تشكيل مهارات اللغة العربية لدى الطلاب، وخاصة في الصف السابع. وذلك بالنظر إلى التحديات والاحتياجات في عملية التعلم، حاولت الباحثة لتحسين قدرات الطلاب على فهم وتطبيق هذه التحديات وجوه. يسعى هذا البحث إلى تطوير كتاب الجيب كمصاحب كتاب اللغة العربية لتحسين المهارات اللغوية بامدرسة الحميدية المتوسطة الإسلامية، ووصف صلاحيته، وفعالية استخدامه. فنتائج البحث في هذه الدراسة هي (1) استخدم بحث التطوير هذا نموذج التطوير Borg & Gall، والخطوات التي قامت بها الباحثة هي تحليل الاحتياجات، والدراسة المكتبية، والدراسة الميدانية، واختيار المواد، وتطوير المنتج، واختبار الخبراء، والتصحيح، وتجربة المنتج وتحسين المنتج النهائي. أدى تطوير هذه المادة التعليمية إلى إنشاء كتاب الجيب كمصاحب كتاب اللغة العربية يتكون من ثلاث وحدات، (2) تم إجراء اختبار الصلاحية الذي يتضمن اختبار الخبراء في جانبين رئيسيين: صلاحية المادة وصلاحية الوسائل. وكانت نتائج اختبار صلاحية المادة 70%، في حين بلغت نتائج اختبار صلاحية الوسائل 90.8%، (3) حصل كتاب الجيب على فئة فعالة للاستخدام كوسيلة تعليمية لطلاب الصف السابع بمدرسة الحميدية المتوسطة الإسلامية. أظهرت نتائج الاختبار أن قيمة t المحسوبة أكبر من جدول t، أي أن t المحسوب هو -24,948 بينما جدول t هو 2,060.